Real time dispatching of bus to improve transfers. - Li, Qing. (University of Ottawa (Canada), 2001)
The purpose of this research is to provide insight into the effectiveness of certain real time dispatching control actions on service reliability for transfer from a high frequency bus route to a low frequency bus route. A model of the operation of 2 connected bus routes was built based on data from real bus routes operated by OC Transpo in Ottawa, and a simulation program was designed and developed. This simulation program was used to conduct experiments to compare different control actions to improve transfer effectiveness, to test the impacts of the bus threshold on passenger waiting time and to evaluate the AVL detector location. We defined an objective function---cost/benefit function, to measure the system performance of the above cases. This objective function considered 2 important factors: number of passengers relevant to transfer and waiting time relevant to control. The research and simulation experiments suggested that real time monitoring technologies can improve the transit bus transferring significantly without preplanned timed transfer. The detector location is determined by feeder line headway primarily and the connecting bus holding threshold secondarily. Without considering the hard requirements from outside system, the bus holding threshold should not be greater than the feeder line headway.
Keywords: Transportation.